HSF1 Alleviates Brain Injury by Inhibiting NLRP3-Induced Pyroptosis in a Sepsis Model - Yi-fu He; Xi-min Hu; Md. Asaduzzaman Khan; Bo-yao Yu; Yi-cun Sheng; Xian-zhong Xiao; Xin-xing Wan; Si-pin Tan; Kun Xiong (Mediators of Inflammation)
Background. Sepsis, which could cause a systemic inflammatory response, is a life-threatening disease with a high morbidity and mortality rate. There is evidence that brain injury may be related to severe systemic infection induced by sepsis. The brain injury caused by sepsis could increase the risk of mortality in septic patients, which seriously affects the septic patient’s prognosis of survival. Although there remains a focus on sepsis research, clinical measures to prevent and treat brain injury in sepsis are not yet available, and the high mortality rate is still a big health burden. Therefore, it is necessary to investigate the new molecules or regulated pathways that can effectively inhibit the progress of sepsis. Objective. NLR family pyrin domain-containing 3 (NLRP3) increased in the procession of sepsis and functioned as the key regulator of pyroptosis. Heat shock factor 1 (HSF1) can protect organs from multiorgan dysfunction syndrome induced by lipopolysaccharides in mice, and NLRP3 could be inhibited by HSF1 in many organs. However, whether HSF1 regulated NLRP3 in sepsis-induced brain injury, as well as the detailed mechanism of HSF1 in brain injury, remains unknown in the sepsis model. In this research, we try to explore the relationship between HSF1 and NLRP3 in a sepsis model and try to reveal the mechanism of HSF1 inhibiting the process of brain injury. Methods. In this study, we used wild-type mice and hsf1-/- mice for in vivo research and PC12 cells for in vitro research. Real-time PCR and Western blot were used to analyze the expression of HSF1, NLRP3, cytokines, and pyrolytic proteins. EthD-III staining was chosen to detect the pyroptosis of the hippocampus and PC12 cells. Results. The results showed that HSF1 is negatively related to pyroptosis. The pyroptosis in cells of brain tissue was significantly increased in the hsf1-/- mouse model compared to hsf1+/+ mice. In PC12 cells, hsf1 siRNA can upregulate pyroptosis while HSF1-transfected plasmid could inhibit the pyroptosis. HSF1 could negatively regulate the NLRP3 pathway in PC12 cells, while hsf1 siRNA enhanced the pyroptosis in PC12 cells, which could be reversed by nlrp3 siRNA. Conclusion. These results imply that HSF1 could alleviate sepsis-induced brain injury by inhibiting pyroptosis through the NLRP3-dependent pathway in brain tissue and PC12 cells, suggesting HSF1 as a potential molecular target for treating brain injury in sepsis clinical studies.